G473(P) Case report: The treatment challenges in the management of an exclusively breastfed infant with new onset type I diabetes. (27th April 2016) - Gallagher, K; Thalange, N
Abstract : Objective: To describe the treatment challenges in the management of an exclusively breastfed infant with new onset type I diabetes. Methods: We present an exclusively breastfed 5 month old male who presented to our emergency department with diabetic ketoacidosis. His mother reports that she found him floppy, pale and unresponsive after a 4 day history of vomiting. He was in severe shock, requiring multiple fluid boluses via the intraosseous route. He was hyperglycaemic with ketosis and severe acidosis (pH 6.871, PCO2 3.19, HCO3 4.4, BE –26.9). In view of fluctuating conscious level he was ventilated and transferred to paediatric intensive care unit. After 3 days, his glucose and ketones normalised and he was extubated. Results: Four days after initial presentation, he was switched from IV insulin to subcutaneous insulin detemir (1.0u daily) and aspart (0.5u as required), with oral glucose gel for hypoglycaemia (<4 mmol/L). However glucose levels varied between 2.6 mmol/L and 21.5 mmol/L and he was commenced on continuous glucose monitoring (CGM). In view of the impracticality of carbohydrate counting, he was commenced on correction boluses of aspart, for glucose >14 mmol/L. After 8 days he was commenced on an insulin pump (Total basal insulin 0.8 u/day), with periodic correction boluses as required, with a correction target of 7 mmol/L. With the assistance of CGM, we have refined his basal rate, and he is now stable with fewer glycaemic excursions (7 day glucose average 9.8 mmol/L). Conclusion: At 5 months old, this exclusively breastfed baby with type I diabetes presented particular challenges. His blood glucose measurements were extremely variable with particular difficulties faced managing hypoglycaemia. As an exclusively breastfed male, the options include dextrose gel and breastfeeding where possible. We recommend the combination of an insulin pump, coupled with CGM and "rescue" correction boluses as the most practical approach to management.